(untitled) (Innovation & Development in Engineering and Applied Science, 2021)
A scientific base is established on the topics of linear, circular and elliptical polarization, Poincaré sphere, Jones and Stokes vectors and Moeller matrices. This scientific foundation helps in understanding the phenomenon and indicates the size of the task and the optical assembly to design and build. The image of a nearby planar object lights up and reflected from a dielectric surface, filtered with an analyzer polaroid to be captured by a CCD, and stored. The evaluation of the changes in a said image is subject to the analysis of the degree of polarization of its parts through algorithms and constitutes the objective of this work. The importance of knowing adequate tools for the acquisition and analysis of images is fundamental, so it was necessary to establish comparison criteria that allow greater versatility when processing the images obtained, MATLAB is one of them, it helps to develop its own algorithm for binarization, segmentation, transformation and comparison of the images, this allows to know the indices of differences that exist between them, this result is expressed as a change matrix.